2022
DOI: 10.26603/001c.31876
|View full text |Cite
|
Sign up to set email alerts
|

Patellofemoral Joint Loading During the Performance of the Forward and Side Lunge with Step Height Variations

Abstract: Background Forward and side lunge exercises strengthen hip and thigh musculature, enhance patellofemoral joint stability, and are commonly used during patellofemoral rehabilitation and training for sport. Hypothesis/Purpose The purpose was to quantify, via calculated estimates, patellofemoral force and stress between two lunge type variations (forward lunge versus side lunge) and between two step height variations (ground level versus 10 cm platform). The hypotheses wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…Araştırmacılar, iniş fazında eklem açısının yer reaksiyon kuvvetine etki ettiği ve açılanma azaldıkça yer reaksiyon kuvvetinin azaldığını belirtmişlerdir. 21 Baskın olmayan ayakta konsantrik fazda yer tepki kuvvetinin baskın ayağa oranla yüksek çıkması, sporcuların baskın olmayan ayaklarının daha yüksek yer tepki kuvvetleri ürettiğini düşündürmektedir. İlerleyen çalışmalarda baskın ayak ile baskın olmayan ayak arasındaki farkın azaltılmasına yönelik antrenmanlar önerilebilir.…”
Section: Sonuçunclassified
“…Araştırmacılar, iniş fazında eklem açısının yer reaksiyon kuvvetine etki ettiği ve açılanma azaldıkça yer reaksiyon kuvvetinin azaldığını belirtmişlerdir. 21 Baskın olmayan ayakta konsantrik fazda yer tepki kuvvetinin baskın ayağa oranla yüksek çıkması, sporcuların baskın olmayan ayaklarının daha yüksek yer tepki kuvvetleri ürettiğini düşündürmektedir. İlerleyen çalışmalarda baskın ayak ile baskın olmayan ayak arasındaki farkın azaltılmasına yönelik antrenmanlar önerilebilir.…”
Section: Sonuçunclassified
“…Previous biomechanical studies have evaluated patellofemoral joint peak force and stress during daily living activities such as walking, 4,23 running, 22 stairs, 3,6 and a few common exercises including jumping, 7 squats, 17,28,38 and lunges. 15,16,18 Yet patellofemoral joint loading profiles remain unknown for a majority of exercises commonly used in patellofemoral or anterior knee pain rehabilitation. 1,5,11,13,27,35,40 Additionally, no studies have reported how patellofemoral joint loading during the large collection of rehabilitation exercises compares with routine walking and running in the same individuals.…”
mentioning
confidence: 99%